Albendazole increases the inflammatory response and the amount of Em2-positive small particles of Echinococcus multilocularis (spems) in human hepatic alveolar echinococcosis lesions. - Franz J Ricken; Juliane Nell; Beate Grüner; Julian Schmidberger; Tanja Kaltenbach; Wolfgang Kratzer; Andreas Hillenbrand; Doris Henne-Bruns; Peter Deplazes; Peter Moller; Peter Kern; Thomas F E Barth (Public Library of Science (PLoS), 2017)
Alveolar echinococcosis (AE) is caused by the metacestode stage of Echinococcus multilocularis. The inflammatory response to this infection is influenced by the interaction of the parasite with the host. We aimed to analyze human liver lesions infected with Echinococcus multilocularis and the changes of the cellular infiltrates during albendazole (ABZ) treatment.We analyzed liver tissue samples from 8 untreated patients, 5 patients treated with two daily doses of 400 mg ABZ for up to two months and 7 patients treated for more than two months with the same ABZ therapy. A broad panel of monoclonal antibodies was used to characterize the lesion by immunohistochemistry. A change in the cellular infiltrate was observed between the different chemotherapy times. During the initial phases of treatment an increase in CD15+ granulocytes and CD68+ histocytes as well as in small particles of Echinococcus multilocularis (spems) was observed in the tissue surrounding the metacestode. Furthermore, we observed an increase in CD4+ T cells, CD20+ B cells and CD38+ plasma cells during a longer duration of treatment.ABZ treatment of AE leads to morphological changes characterized by an initial, predominantly acute, inflammatory response which is gradually replaced by a response of the adaptive immune system.